Life on the Mississippi ? - Twain, Mark (New York : Penguin Books, 1984)
Offers a history of the river, describes Twain's experiences as a riverboat pilot, and shares tall tales, character sketches, and observations about the Mississippi.
Keywords: Mississippi River -- Description and travel